An assessment of HIV&AIDS prevention and management programmes in the Northern region of Ghana: a case study of the Tamale Metropolis and the Yendi Municipality. - Konlaa, Jacob Dindiok (2011)
A Thesis submitted to the School of Graduate Studies Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of Master of Science in Development Policy and Planning